Bacterial diversity of soil irrigated with Gypsiferous mine water as determined by culture-dependent and -independent techniques - Cloete, T.E. (Thomas Eugene), 1958- (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2010.